E-Municipality and Public Relations in Digitalized Cities: An Interpretive Content Analysis on TR42 Region Municipalities - İlayda Uzun; Hasan Tutar (Yeni Medya)
In an age where the understanding of non-urbanization has moved to the digital level, the need to benefit from digital tools for effective governance in municipalities brings the phenomenon of e-municipality to the agenda. The primary purpose of this research is to investigate the multifaceted interaction between e-municipality and Public Relations in digitalizing cities and examine how technology-oriented urban governance shapes public relations dynamics. The sample of this study, designed with the hermeneutic content analysis method, consists of Bolu, Düzce, Sakarya, Kocaeli, and Yalova, which are classified as the TR42 region. The websites of the municipalities in question in the research were analyzed with interpretive content analysis techniques regarding Security/Privacy, Citizen and Social Interaction, and operational-formal informational and Strategic Skill variables and various suggestions were made. Research results show that e-municipality redefines traditional public relations concepts in digitalizing cities. Findings show that e-municipality offers essential opportunities to facilitate access to information, strengthening local democracy, enabling citizens' participation in decision-making processes, transparency, and accountability. E-municipality platforms are a powerful public relations tool in that they provide essential opportunities for citizen-municipality interaction and encourage community participation. Integrating e-municipality and public relations in digitalizing cities points to a transformative change in urban governance. In this process, effective public relations strategies emphasize communication and active citizen participation, increasing the importance of adapting to this dynamic environment. From this point of view, the volume of policymakers and local governments to take measures to eliminate digital literacy inequalities increases.